2015
DOI: 10.1530/rep-14-0269
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones improves endometrial barrier through tight junction gene expression

Abstract: Contamination with bacterial endotoxin causes the disruption of the tight junction (TJ) barrier. We investigated the ameliorative effect of dietary flavonoids genistein (Ge) and daidzein (Di) in normal or lipopolysaccharide (LPS)-induced disruption of epithelial barrier function of the endometrium. Using the immortalized porcine glandular endometrial epithelial cells (PEG), transepithelial electrical resistance (TER) and FITC-dextran flux (FD-4) across the monolayer were measured. The mRNA expression of TJ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…It had been reported that estrogen possessed protective effects on the blood‐brain barrier function in mice and improved the TJs damage 15,35 . Similarly, soy isoflavones had good effects on promoting and restoring LPS‐induced damage to the endometrial barrier function 36 . The role of estrogen signaling in immune regulation had historically been studied in terms of the classical estrogen receptors ERα and ERβ 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that estrogen possessed protective effects on the blood‐brain barrier function in mice and improved the TJs damage 15,35 . Similarly, soy isoflavones had good effects on promoting and restoring LPS‐induced damage to the endometrial barrier function 36 . The role of estrogen signaling in immune regulation had historically been studied in terms of the classical estrogen receptors ERα and ERβ 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin enhances intestinal barrier in Caco-2 cells through the elevation of claudin-4 [34] and through the assembly of zonula occludens-2, occludin, and claudin-1 [35]. Genistein and daidzein protect lipopolysaccharide-induced disruption of barrier function in glandular endometrial epithelial cells through the elevation of claudin-3, -4, and -8 [36]. In contrast, the effects of flavonoids on the pathophysiological function and expression of claudins in cancer cells have not been examined well.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated a beneficial role in intestinal morphologic structure and barrier function. Kiatprasert et al (31) reported that treatment with soy isoflavones may promote and restore the impaired endometrial barrier function by increasing the gene expression of tight junction-associated genes in lipopolysaccharide-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%